Effective dose from radiation exposure in medicine: Past, present, and future. (November 2020) - Martin, Colin J.; Harrison, John D.; Rehani, Madan M.
Highlights: Effective dose (E) provides a measure of potential risk in terms of health detriment. E is calculated as a risk-weighted average of organ doses. E is applied to a reference person, but patient-specific calculations can be done. E is useful as a guide in making everyday decisions about patient imaging. E should be derived using the most up-to-date phantoms and weighting factors. Abstract: Effective dose ( E ) has been developed by the International Commission on Radiological Protection (ICRP) as a dose quantity with a link to risks of health detriment, mainly cancer. It is based on reference phantoms representing average individuals, but this is often forgotten in its application to medical exposures, for which its use sometimes goes beyond the intended purpose. There has been much debate about issues involved in the use of E in medicine and ICRP is preparing a publication with more information on this application. This article aims to describe the development of E and explain how it should be used in medicine. It discusses some of the issues that arise when E is applied to medical exposures and provides information on how its use might evolve in the future. The article concludes with responses to some frequently asked questions about uses of E that are in line with the forthcoming ICRP publication. The main use of E in medicine is in meaningful comparison of doses from different types of procedure not possible with measurable dose quantities. However, it can be used, with appropriate care, as a measure of possible cancer risks. When considering E to individual patients, it is important to note that the dose received will differ from that assessed for reference phantoms, and the risk per Sv is likely to be greater on average in children and less in older adults. Newer techniques allow the calculation of patient-specific E which should be distinguished from the reference quantity.